2013
DOI: 10.29244/jitkt.v5i1.7766
|View full text |Cite
|
Sign up to set email alerts
|

EMBRYONIC DEVELOPMENT AND HATCHING EGGS RATIO OF BLACKSADDLED CORAL GROUPER (Plectropoma laevis) AT DIFFERENT TEMPERATURE MEDIA

Abstract: In seed production, the success of spawning and egg production is very important to mantain the cultivating sustainability. The quantity and quality of the blacksaddled coral grouper eggs should be properly manipulated to produce the higher values. The purpose of this study was to determine the effect of different temperatures on the results of hatch success (embryo development, incubation time, hatching rate and larvae abnormality). The eggs used were obtained from natural spawning and collected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The newly hatched larvae and unhatched eggs were counted from each tank. The hatching rate (HR, %) was calculated using a formula explained by Andriyanto et al (2013):…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly hatched larvae and unhatched eggs were counted from each tank. The hatching rate (HR, %) was calculated using a formula explained by Andriyanto et al (2013):…”
Section: Discussionmentioning
confidence: 99%
“…Wabo et al (2011) examined unsuccessfully hatched eggs of Heligmosomoides bakeri which possess blastomeres destroyed when eggs immersed in a high dose of aqueous and ethanolic extract of papaya seeds. The low hatching rate is believed to be influenced by the carotene alkaloid content in papaya leaf extract, which is toxic and could interfere mechanistically with the hatching enzyme function and it inhibits egg hatchability (Supriati et al, 2010;Andriyanto et al, 2013;Ardhardiansyah et al, 2017;Firdaus et al, 2017;Haser et al, 2018). We argued that the absence of this effect on eggs treated in low doses of papaya leaf Optimizing embryonic development, egg hatchability ..... (Teuku Fadlon Haser) extracts may be due to inadequate concentration to pass through the eggs membrane system, therefore it becomes less potent to the embryo.…”
Section: Abnormalitiesmentioning
confidence: 99%
“…In high temperature metabolic processes occur more rapidly causing the development of embryos in the shell more active than low temperature, thus accelerating the hatching process. The temperature of incubation media will stimulate the embryo metabolism process, so that embryo development in higher incubation media will be faster (Andriyanto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The best temperature range during the incubation for hatching of fish eggs depends on the species of fish. The best incubation temperature for Pagrus major eggs is 12.7 to 29.7°C (Apostolos and Kitajima, 1994), Oreochromis karongae between 25 and 29°C (Valeta et al, 2013), Plectropoma laevis at 30 o C (Andriyanto et at, 2013), Anabas testudineus at 28 o C (Putri et al, 2013), Lutjanus johnii at 30 o C (Sugiarto et al, 2015), Hexagrammos otakii 12-16°C (Fawen et al, 2015), Lates calcarifer at 30 o C (Thépot and Jerry, 2015). The results of that studies showed, temperature can affect of hatching egg fish.…”
Section: Introductionmentioning
confidence: 99%